As contribuições das metodologias ativas nas práticas de ensino-aprendizagem no componente de História no curso de Edificações no ensino médio integrado do IFAM Campus Manaus Centro - Monteiro, Alex Sandro dos Santos (2025)
Active Methodologies, the subject of the proposed study, are key approaches to making History teaching meaningful and engaging. The use of these methodologies is essential to achieving better outcomes in light of the current climate of historical and scientific denialism. This work presents a situational analysis, seeking to identify the most effective methodology for History teaching. It is a quantitative-qualitative research study that values the research subjects in their qualitative and quantitative aspects, with a descriptive and explanatory nature. The study addresses the legal, theoretical, and methodological aspects of Professional and Technological Education (EPT) in the context of Integrated High School, specifically the Building Construction course at IFAM Campus Manaus-Centro (CMC). It is based on research from the Professional Master’s Program in Professional and Technological Education (PROFEPT), within the line of Practice Studies. Field research was conducted using Field Notebooks, Printed and Digital Forms with semi-open questions, as well as interviews with semi-open questions. For data analysis, Discursive Textual Analysis (ATD) was employed.The objective of this study is to analyze which active methodologies can be implemented in the classroom and their contributions to the human, omnilateral (Ciavatta, 2014), and comprehensive education of students in Integrated High School with EPT at Campus Manaus-Centro. Additionally, it aims to examine, through current legislation, the concept, theoretical assumptions, and importance of integrating high school with EPT for the holistic human development of individuals (Freire, 1987); to explore, through literature, active methodologies their concept, types, importance, and applicability; to present, via field research, how students perceive History classes and their main challenges in the teaching and learning process; and finally, to develop an educational product focused on active methodologies as a support tool for improving the teaching and learning process in History classes, serving as a resource for educators. Thus, the research emphasizes that Active Learning Methodologies (Bacich and Moran, 2018) are highly valuable in History teaching, contributing to a human, omnilateral, comprehensive, polytechnic (Ciavatta, 2014), and critical education core principles of Integrated High School (Frigotto, 2018) within Professional and Technological Education in Federal Institutes.